Determinan Financial Distress pada Perusahaan Sektor Healthcare - Melati, Merry Mawar; Espa, Vitriyan; Yantiana, Nella (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
A company's financial condition is a crucial factor that determines the survival and growth of a company. Financial distress is a condition where a company is unable to meet its financial obligations on time, which often leads to bankruptcy. Early identification of the factors that influence financial distress becomes very important to prevent wider negative impacts, not only for the company itself but also for other stakeholders, including investors, employees, and business partners. This study aims to analyze the effect of profitability, liquidity, and firm size on financial distress in healthcare companies listed on the Indonesia Stock Exchange. This research uses a quantitative method. The research was conducted on Healthcare Companies Listed on the Indonesia Stock Exchange in 2018-2022, with the object of the research being healthcare companies listed on the Indonesia Stock Exchange in 2018-2022. The results show that the significance value of ROA (0.047) is smaller than alpha (0.05), indicating that individually, the ROA variable has a significant effect on Financial Distress (FD). The significance value of CR (0.000) is much smaller than alpha (0.05), indicating that individually, the CR variable has a very significant effect on Financial Distress (FD). The significance value of FS (0.137) is greater than alpha (0.05), indicating that individually, the FS variable has no significant effect on Financial Distress (FD). Overall, the results show that the profitability (ROA) and liquidity (CR) variables have a significant effect on Financial Distress (FD), while the firm size (FS) variable has no significant effect